ANALISIS TUTURAN BERMUATAN PENCEMARAN NAMA BAIK DALAM FACEBOOK - Adhani, Agnes (Widya Warta, 2018)
The purpose of this study was to know and to describe (1) the type of speech, (2) the linguistic unit of speech markers, and (3) the violation of courtesy principles in speech containing defamation in Facebook. This study was qualitative descriptive research with the data of speech from two Facebook accounts. The data were analyzed by the techniques of substitution, expansion, and paraphrase. The results of this study showed that (1) there were types of direct and indirect speech, (2) there were eleven linguistic units as the markers of defamation, namely 9 sentences, 1 phrase, and 1 word, and (3) there was a violation of the politeness principle to the tact maxim, the generosity maxim, the sympathy maxim, and the agreement maxim.